Investigation on the distribution and role of intermetallic aggregates in influencing the mechanical strength of the friction stir welded AZ91C Mg – AA6061 Al alloy joints - PJ Lokesh Kumar; P Sevvel; TG Loganathan; D Prakash (Materials Research Express, 2023)
In this experimental work, 6 mm thick plates of distinctive metal alloys namely AZ91C Mg alloy and AA6061 Al alloy were joined using the FSW process, and fabricated joints were investigated to apprehend the impact of convoluted interfaces and their distribution in the nugget zone and the role of intermetallic aggregates in impacting the mechanical properties of the joints. Employment of tool rotational speeds higher than 1100 rpm has fabricated AZ91C Mg–AA6061 Al joints possessing inter–infiltrating structures along with curved junctures, promoting micro-void unification (MCU) on the fractured regions owing to mechanical-related interlocking. AZ91C Mg–AA6061 Al joints have experienced tensile-related failure along the layer of intermetallic and in the regions of inter–infiltrating components nearer to the side of Al parent metal. Joints exhibiting superior strength have been attained due to the generation of intricate interfaces at the joint region, which in turn has contributed to the mechanical-based interlocking. Highest tensile strength exhibited by the joint was 242 MPa, which is nearly 78% of the strength of the parent 6061 Al alloy (310 MPa).